2016
DOI: 10.2486/indhealth.2016-0057
|View full text |Cite
|
Sign up to set email alerts
|

Social and household factors affecting child health checkup attendance based on a household survey in Japan

Abstract: Child health checkups are an important public service to support children’s development; however, many children do not attend all the child health checkups that are required by maternal and child health law (i.e., at 1 month, 4 months, 1 and a half years, and 3 years of age). This study aimed to identify social and household factors influencing child health checkup attendance. We used data from a longitudinal household panel study in Japan. The total number of subjects was 2,612 children. We extracted numerous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Third, we could not identify what kinds of articles or magazines were associated with avoiding children’s health checkups. Finally, although we selected the covariates from a previous similar study [ 23 ], unmeasured confounders, such as the availability of childcare services, parents’ working hours, and the number of paid days off work, might have caused a bias in the association.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, we could not identify what kinds of articles or magazines were associated with avoiding children’s health checkups. Finally, although we selected the covariates from a previous similar study [ 23 ], unmeasured confounders, such as the availability of childcare services, parents’ working hours, and the number of paid days off work, might have caused a bias in the association.…”
Section: Discussionmentioning
confidence: 99%
“…The covariates were selected from the previous study that examined factors influencing child health checkups using data from a longitudinal household panel survey in Japan [ 23 ]. The study indicated that maternal age at birth, birth order, parents’ educational attainment, household income, the frequency of help from grandmothers, and the number of communicating neighbors were factors that influenced health checkup attendance.…”
Section: Methodsmentioning
confidence: 99%
“…Localized social interaction could help migrants to be better familiar with the local culture, customers, decrease exclusion of mainstream social settings and have a strong sense of belonging to the inflow areas. On the other hand, migrants could obtain local information from their neighbors, including information on how to use the local health services ( 16 , 27 ). A study had suggested that mothers who were socially integrated can obtain relevant oral health information from their surroundings individuals, which indirectly improves children's oral health service utilization ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Various factors have been found related to missed appointments, including: patient characteristics (e.g., age, sex, ethnicity, socioeconomic status); family logistics (e.g., working parents, care of other children); clinic accessibility (e.g., distance, transportation, opening hours); and administrative factors (e.g., cost, waiting period, communication errors). [14][15][16][17] Furthermore, patients who do not perceive the service as urgent or particularly helpful tend to miss their appointment. 17,18 On the other hand, being referred for assessment by a physician has been found to have a significant positive impact on keeping an appointment.…”
Section: Highlightsmentioning
confidence: 99%